Bastee (slum and squatter) settlements of Dhaka City, Bangladesh: a review of policy approaches and challenges ahead - Mohit, Mohammad Abdul (2011)

(untitled)
Dhaka, capital city of Bangladesh, with a population of 12 million, receives 300,000 to 400,000 rural migrants annually. During last three decades, city population has grown over 7%, annually. Bastee population of city has grown from 1.0 million in 1990 to 3.4 million in 2005. Several policy approaches such as eviction, resettlement and upgrading, were adopted to deal with bastee settlements of Dhaka since 1975. These policies approaches were not very effective, because the scale of the problem is very large, which provides future challenges to deal with the bastee situation.